The Effect of Weather Variables on Mosquito Activity: A Snapshot of the Main Point of Entry of Cyprus - Drakou, Katerina; Nikolaou, Thessalia; Vasquez Christodoulou, Marlen; Petric, Dusan; Michaelakis, Antonios; Kapranas, Apostolos; Papatheodoulou, Athina; Koliou, Maria (My University, 2020)
Mosquitoes are vectors of pathogens, causing human and animal diseases. Their ability to adapt and expand worldwide increases spread of mosquito-borne diseases. Climate changes contribute in enhancing these "epidemic conditions". Understanding the effect of weather variables on mosquito seasonality and host searching activity contributes towards risk control of the mosquito-borne disease outbreaks. To enable early detection of Aedes invasive species we developed a surveillance network for both invasive and native mosquitoes at the main point of entry for the first time in Cyprus. Mosquito sampling was carried out for one year (May 2017-June 2018), at bimonthly intervals around Limassol port. Morphological and molecular identification confirmed the presence of 5 species in the study region: Culex. pipiens, Aedes detritus, Ae. caspius, Culiseta longiareolata and Cs. annulata. No invasive Aedes mosquito species were detected. The Pearson's correlation and multiple linear regression were used to compare number of sampled mosquitoes and weather variables for three most numerous species (Cx. pipiens, Ae. detritus and Ae. caspius). The population densities of the most numerous species were highest from February to April. Number of Cx. pipiens (-0.48), Ae. detritus (-0.40) and Ae. caspius (-0.38) specimens sampled was negatively correlated with average daily temperature. Monthly relative humidity showed positive correlation with the numbers of the species sampled, Cx. pipiens (0.66) Ae. detritus (0.68), and Ae. caspius (0.71). Mosquito abundance of Cx. pipiens (0.97) and Ae. detritus (0.98) was strongly correlated to seasonal precipitation as well. Our work is a stepping stone to further stimulate implementation of International Health Regulations and implementation of early warning surveillance system for detection of invasive Aedes mosquitoes, native mosquitoes and arboviruses they may transmit. A network for the surveillance of both invasive and native mosquito species at the main point of entry for the first time in Cyprus was developed. Number of mosquitoes sampled was correlated with weather factors to identify parameters that might predict mosquito activity and species distribution to the prevention of international spread of vector mosquitoes and vector-borne diseases.
Keywords: Ae. caspius; Ae. detritus; Aedes invasive species; Cx. pipiens; Precipitation; Relative humidity; Surveillance; Temperature